Russian Federation : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Russia is in its seventh year of robust economic growth. This strong performance was ignited by the sharp depreciation in the wake of the 1998 crisis, and subsequently sustained by large terms-of-trade gains, in combination with increased political and macroeconomic stability. Higher output and investment in the oil sector have been key conduits of the broad-based recovery, which is still running its course. Monetary policy remains relatively lax. The economy is expected to continue to grow robustly, although not at the pace seen before last year's slowdown.